First identification of Ewing's sarcoma‐derived extracellular vesicles and exploration of their biological and potential diagnostic implications. (4th May 2013) - Miller, Isabella V.; Raposo, Graca; Welsch, Ulrich; Prazeres da Costa, Olivia; Thiel, Uwe; Lebar, Maria; Maurer, Martina; Bender, Hans‐Ulrich; von Luettichau, Irene; Richter, Günther H. S.; Burdach, Stefan; Grunewald, Thomas G. P.
<x xml:space="preserve">Abstract</x> We report on the first identification of exosomes derived from Ewing's sarcoma cell lines, which contain specific transcripts including EWS‐FLI1 that are suitable for sensitive detection of ES exosomes in a pre‐clinical model for patient plasma. Microarray analysis revealed an exosomal transcriptional signature involved in G‐protein‐coupled signalling, neurotransmitter signalling and stemness. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>